Temperature-Humidity Index Values and Their Significance on the Daily Production of Dairy Cattle in the North African Arid Region - Hanane Djelailia; Naceur M’hamdi; Bayrem Jemmali; Rachid Bouraoui; Taha Najar (Al-Qadisiyah Journal For Agriculture Sciences, 2023)
Climate changes affect the economic viability of livestock. Therefore, this study aimed to characterize the heat stress in Holstein cattle raised in the arid region of Tunisia as well as to evaluate the effect of the temperature-humidity index (THI) on daily milk production and components. For this reason, 76940 monthly individual records collected from 1995 to 2018 from 3056 Holstein cows were used. THI calculated from ambient temperature and relative humidity was used as a measure of heat stress. To study the effect of THI on milk production, a repeated measures linear mixed model was used. Results showed a significant (P<0.01) decrease in daily milk yield, daily protein, and fat content in all cow’s parity classes. For each point increase of the THI values beyond 64, milk yield, fat, and protein contains decreased by 0.32 kg, 0.09, and 0.06 %, respectively. Moreover, when the THI value varied from 64 to 85, fat content decreased by 29 %, protein by 17 %, and milk production by 30 %. Heat stress impact negatively milk production and milk components of dairy cows. These results can be a way to improve the length of productive life for Holstein dairy cattle in the hard climate. Serious management strategies are needed to improve dairy cow productivity and minimize the heat stress impact.